MECHANICAL ANISOTROPY OF COLD-ROLLED ST-37 STEEL PLATE UNDER HIGH STRAIN RATES LOADINGS - Perkasa, Rilis Eka; Gunawan, Leonardo; Santosa, Sigit Puji; Afdhal, Afdhal (International Journal of Mechanical Engineering Technologies and Applications, 2023)
Cold rolling process in metal could increase its strength and hardness, but also induces mechanical anisotropy. This is caused by unresolved plastic strain and microstructural changes caused by plastic deformation exerted by pair of rolls at a relatively low temperature. This research aims to provide understandings on anisotropic and strain rate sensitive behaviour of St-37 mild steel. The microstructure of rolled and unrolled St-37 plate were observed in 3 directions relative to the rolling direction. The cylindrical specimens were then prepared from rolled plate with 33.3% reduction in the orientation of 0o, 45o, and 90o relative to the rolling direction. Specimens were also prepared from unrolled plate as comparison in the same directions. These specimens were then tested in compression loading, first in quasi-static condition, and then by using Split-Hopkinson Pressure Bar (SHPB) at the strain rate of 1200 s-1. The experimental results in the form of stress-strain curves are used to obtain the parameters of Simplified Johnson-Cook viscoplastic model. The anisotropy of yield strength in rolled specimens could be seen on both quasi-static and high strain rate condition, where the highest strength found on the specimens perpendicular to the rolling direction. In addition, the effect of cold rolling to the strain rate sensitivity of the material were also captured successfully in this study, where specimens from rolled plate show less strain rate sensitivity compared to the unrolled specimens.